High-index and low loss polyethylene terephatate optical waveguides - Low, Andy L. Y.; Singh, Ghanshyam K.; Yong, Y. S. (2004)
In this paper, the fabrication and characterization of a high-index low loss polyethylene terephatate (PET) optical waveguide is presented. Dip-coating technique has been used to fabricate the optical waveguide using PET. Various waveguide properties, such as mode effective refractive index, optical loss, dispersion and waveguide thickness as a function of temperature of waveguides and substrates have been reported. Optical losses of as low as 0.7 dB cm(-1) waveguides can be obtained if the formation temperature can be controlled between 30 and 35degreesC. In addition, we suggested that it is a suitable material for optoelectronic waveguide devices.